PENERAPAN MODAL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SDLB-B NEGERI DUMAI - Yusnimar '; Munjiatun '; Mahmud Alpusari Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The problem in this study is the low learning outcomes PKN fifth grade students SLB-B State Dumai with an average of 65 with a KKM 70 This is due to the lack of student participation in the learning process, as well as the lack of student-student interaction in the learning process, because teachers still use the lecture method . The purpose of this research is to improve learning outcomes PKN class V SLB-B State Dumai. The problem of this study is "What type of application of learning models Cooperative Think Pair Share (TPS) can improve the learning outcomes of students of class V PKN SLB-B State Dumai?" This study is an action research conducted in collaboration between researchers with the homeroom teacher V. The study was conducted in two cycles. In the learning process of Think Pair Share, students are actively involved in the learning process, students exchange ideas and opinions to solve problems so that students can complete the task on time. The results showed an increase in students' learning outcomes PKN class V SLB-B State Dumai held action after learning a model of the type Cooperative Think Pair Share (TPS). It can be categorized low average of 65, while the daily test 64.56 daily test cycle I to cycle II with an average of 81.24. The percentage of all teachers in the first cycle 70.83% with either category, the second cycle to 81.24%, with a very good category,. While the percentage of student activity in the first cycle of 65.56 categorized very well. Based on the results of research and analysis of these data, can disimpulakan that the application of learning models of type Cooperative Think Pair Share (TPS) can improve the learning outcomes of students of class V PKN SLB-B State Dumai.     Keywords: Model, Cooperative Learning, Think Pair Share, TPS, Learning Outcomes Citizenship Education.